The economics of rice (Paddy) production in selected Barangays of Pototan, Iloilo. - De La Cruz, Myrna Lorilla
The poduction function and cost and return analysis in rice production were evaluated. This study covers the town of Pototan. The vicinity is irrigated and situated in a lowland with an average farm size of 1.41 hectare., Cost and return analysis showed that production costs was P19,115.85/farmer/crop while financial profit was valued at P18,518.47/farmer/crop and an economic profit of P11,117.65/farmer/crop. To measure the constraints in rice production, regression analysis, using the Cobb-Douglas production function, was employed. Results showed that the quantity of seeds applied, farm size, and educational attainment significantly affected production. The coefficient of determination (R 2) was 0.80 which means that 80 percent of the variation in farm production was explained by the variables included. The F-statistic rejected the null hypothesis, and subsequently accepted the alternative hypothesis that at least one or more of the independent variables affect production. The sum of regression coefficients (1.29) indicated increasing returns to scale. The optimum level of quantity of seeds to be applied was estimated at 273.28 kg while the optimum farm size was 1.18 ha. Farmers can enhance production by using modern machineries with proper use of inputs. Government assistance in terms of credit and infrastructure facilities will provide the necessary boost to production and profitability.